2020
DOI: 10.3390/nu12082379
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Ketogenic Diet Treatment: Impact of Decanoic Acid and Beta—Hydroxybutyrate on Sirtuins and Energy Metabolism in Hippocampal Murine Neurons

Abstract: The ketogenic diet (KD), a high-lipid and low-carbohydrate diet, has been used in the treatment of epilepsy, neurodegenerative disorders, inborn errors of metabolism and cancer; however, the exact mechanism/s of its therapeutic effect is not completely known. We hypothesized that sirtuins (SIRT)—a group of seven NAD-dependent enzymes and important regulators of energy metabolism may be altered under KD treatment. HT22 hippocampal murine neurons were incubated with two important KD metabolites–beta-hydroxybutyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 87 publications
(116 reference statements)
0
27
0
Order By: Relevance
“…We recently demonstrated that sirtuins (a group of NAD+-dependent enzymes) and the mitochondrial respiratory chain complexes were upregulated in HT22 neurons under C10- and ßHB-incubation [ 39 ]. Lipids serve as energy substrates in the CNS (reviewed in [ 2 ]) and phospholipids such as PE and CL are crucial for the efficient functioning of the respiratory chain and maintaining the mitochondrial membrane potential [ 8 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that sirtuins (a group of NAD+-dependent enzymes) and the mitochondrial respiratory chain complexes were upregulated in HT22 neurons under C10- and ßHB-incubation [ 39 ]. Lipids serve as energy substrates in the CNS (reviewed in [ 2 ]) and phospholipids such as PE and CL are crucial for the efficient functioning of the respiratory chain and maintaining the mitochondrial membrane potential [ 8 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…All red arrows depict the effects of ßHB, and all blue arrows depict the effects of C10. Thin arrows show already published data (adapted from [ 39 ]). Solid thick arrows show the effects of ßHB and C10 on absolute quantities of the depicted cellular lipids.…”
Section: Figurementioning
confidence: 99%
“…A ketogenic diet is neuroprotective through reduction of ROS levels, by increasing mitochondrial uncoupling protein levels and activity [ 436 ], as well as by increasing oxidation of NADH and enhancing mitochondrial respiration [ 437 ]. This diet results in increased SIRT1 levels in mice hippocampal neurons [ 438 ]. Ketosis may also activate SIRT1 due to an increased NAD+/NADH ratio, which in turn can promote autophagy in the brain [ 439 ].…”
Section: The Role Of Sirtuins In Metabolic Tissuesmentioning
confidence: 99%
“…IF leads to ketogenic metabolism, increasing β-hydroxybutyrate levels in serum and CSF [ 162 ]. Interestingly, β-hydroxybutyrate protects against Aβ toxicity [ 163 , 164 ] and protects hippocampal murine neurons [ 165 , 166 ]. Whereas previous studies have reported no significant effects of IF on neuroinflammation, synaptic plasticity or cognitive function in 6-month 5xFAD mice [ 167 ], it has also been shown that IF restores aquaporin-4 polarity, reduces SP deposition and ameliorates cognitive dysfunction in APP/PS1 mice [ 168 ].…”
Section: Diet Inflammation and Gut Microbiota In Ad Modelsmentioning
confidence: 99%